Guide to the new Millennium Development Goals Employment indicators : including the full decent work indicator set (International Labour Office, 2013)
This Guide to the Millennium Development Goals Employment Indicators has been produced as a tool for country level use. It provides definitions, concepts and formulas for each of the new employment indicators, and is part of ILO's wider support to strengthening national-level labour market information and analysis to inform policy-making.